Steganalysis Bukti Digital pada Media Storage Menggunakan Metode GCFIM - Muh Hajar Akbar; Sunardi Sunardi; Imam Riadi (UIN Sunan Kalijaga Yogyakarta, 2020)
Steganography is an anti-forensic technique that allows a criminal to hide information in other messages, so that during an examination it will be difficult to obtain evidence of the crime information. Therefore we need a technique to detect hidden messages in the data. This technique is known as steganalysis. Steganalysis is an anti-steganography science whose main purpose is to study the hiding characteristics of data on digital media and detect the existence of secret messages that are hidden using steganography techniques. The purpose of this study is to apply steganalysis techniques to detect the presence of messages that are hidden in other messages by using the forensic method, namely Generic Computer Forensic Investigation Model (GCFIM). In this study, the process of inserting steganographic messages using the Hiderman application, while the steganalysis process uses the StegSpy application. The results obtained in this study were the process of steganalysis using the help of the StegSpy application proved to be successful in detecting the presence of hidden messages in the five files that were scanned by steganographic messages.